Determination of Norcantharidin in Mouse Tissues by Liquid Chromatography Coupled to Tandem Mass Spectrometry and its Tissue Distribution Study - Zhang, R.; Wang, J.; Yuan, G.; Wei, C.; Liu, X.; Wang, B.; Gao, H.; Guo, R. (Arzneimittelforschung, 2012)
The purpose of this study is to determine the concentrations of norcantharidin (CAS NO: 5442-12-6) in mouse tissues and investigate its tissue distribution after intragastric administration of disodium norcantharidate solution. A highly sensitive and specific liquid chromatography-tandem mass spectrometric (LC-MS/MS) method was developed and validated, using ribavirin (CAS NO: 36791-04-5) as the internal standard (IS). Norcantharidin and IS were extracted from 0.3 mL tissue homogenates using protein precipitation with acetone under acid condition. The analyte was separated on a C18 reverse phase column and analyzed by MS/MS in the multiple reaction monitoring (MRM) mode using ESI with positive ionization, m/z 169→123 for norcantharidin and m/z 267→135 for IS. The developed method was validated over a linear range of concentrations 0.01~5 μg·mL − 1 in liver, lung, kidney, stomach, small intestine, uterus and testis, 0.005~0.5 μg·mL − 1 in heart, spleen and brain, the correlation coefficients (r2) were between 0.9918 and 0.9976. The tissue distribution study result was as follows: The AUC0-t of norcantharidin in tissues was in the order as follows: small intestine, stomach, uterus, kidney, testis, liver, lung, spleen, heart, brain.
Keywords: norcantharidin; tissue distribution; LC-MS/MS